Whats new about lutoids? A vacuolar system model from Hevea latex - DAuzac J; Jacob J L; Prevot J C (Plant Physiology and Biochemistry, 1995)
Lutoids are lysosomal microvacuoles in Hevea brasiliensis latex that are easily isolated by differential centrifugation. Fresh lutoids or reconstituted tonoplast vesicles have been used to demonstrate ATPase and prophosphatase influx proton pumps and an NADH-cytochrome c oxidase efflux proton pump. Various antiports have been described : H+/citrate, H+/basic amino acids, 2H+/Mg2+ and H+/Ca2+. The existence of a 2H+/K+ antiport seems probable and the existence of an ATPase Ca2+ pumps is suspected. An NAD (P) H-quinone reductase producing superoxide anions has also been described on this tonoplast. In addition to the classic range of acid hydrolases of lysosomes, lutoids contain acid and basic defence protein (chitinase/lysozyme (hevamins) and B-glucanase). Hevein is a major protein found in the N-terminal position of several plant proteins of the lectin or chitin-binding type. It is directly involved in latex agglutination and coagulation. This is the first time that an aglutination process has been seen to be involved in latex coagulation. Other lutoid proteins may be linked with storage or stress. The stimulation of industrialscale latex production by applying Ethrel to rubber trees modifies the quantity or activity of lutoid proteins or enzymes. The specific activities of ATPase. pyrophosphatase and chitinases are enhanced. Ethylene affects the quantity of the corresponding transcripts, at least for chitinase and hevein. Several lutoid proteins, including hevein and hevamin, are allergenic and are therefore of particular importance for certain items manufactured in latex.
Source Year: 1996